The Role of Management Commitment and Leadership in Implementing Green HRM in Hotels - Dyah Palupiningtyas; Krisnawati Setyaningrum Nugraheni; Ray Octafian; Aletta Dewi Maria; Yema Charista Zelda; Sajia Ferdousi; Dita Aulia Rachma Nurul Farida; Hesky Ilham Ikhlasandi (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This study aims to investigate how top management commitment and leadership style influence the effectiveness of implementing green HRM practices in the hospitality industry. The study employs a qualitative approach by conducting case studies in selected hotels across Asian countries. Data is collected through in-depth interviews with hotel leaders and HR staff. Thematic analysis is performed to identify important patterns and insights related to the role of commitment and leadership in implementing green HRM initiatives. The results of this study are expected to provide a better understanding of the key factors that determine the successful adoption of green HRM practices in the Asian hospitality industry.